STRATEGI PENGELOLAAN EKONOMI KELUARGA PADA MASYARAKAT KEPULAUAN KECAMATAN TUPA’BIRING KABUPATEN PANGKEP (SUATU ANALISIS GENDER) - Mustadjar, Musdaliah (Makassar Journal of Social Sciences, 2013)
This study aims to determine how the family's economic management strategy fishing communities in Sub Tupa'biring Pangkep. Some things that will be revealed is the profile of women fishermen; the role and function of wives of fishermen in his home life; socio-cultural background conditions the wife work outside the domestic sphere; partnership relationship between husband and wife, especially in the allocation of work time and decision-making as well as its relationship with the welfare of the family.  This study is an ex post facto study, informants purposively taken as many as 50 people, consisting of 25 husbands and 25 wives. Data were collected through observation and interviews using a structured interview guide, and then analyzed by descriptive qualitative frequency table and table percentage is equipped with the interview.  The results of this study indicate that: (1) The wives of fishermen on the islands community subdistrict Tupa'biring Pangkep work involved the public domain because of socio-cultural environment supports, vice versa, the husband worked diranah domestic help. (2) The principle Sibali - Akkareso and meaning Siri ' underlying mutual cooperation between husband and wife is one with a reflection on the allocation of work time and in decision-making, this is the family's economic management strategies island communities District of Tupa'biring Pangkep, and (3) The condition of the fishing community households Tupa'biring District of the islands are in the living standards of families in One